THE IMPACT OF MINING EXCAVATIONS (VOIDS) ON THE WATER QUALITY MANAGEMENT IN THE NORTH KALIMANTAN PROVINCE - Ardian, Sandy; Aipassa, Marlon Ivanhoe; Oktaviani, Reva; Imang, Ndan; Devy, Shalaho Dina; Susilo, Heru Ivanhoe; Kristiningrum, Rochadi Kristiningrum; Sarwono, Edy Kristiningrum; Arifin, Dawamul Ivanhoe (Gorontalo Journal of Forestry Research, 2024)
The presence of a coal mining business permit not only has an economic impact but can also cause environmental problems. The objectives of this research are (1) to analyze the impact of PT XXX's overflowing voids on water management and water quality, and (2) to carry out spatial analysis, mapping and estimation of coal reserves that cannot be extracted by PT YYY. The research method is a case study selected by purposive sampling at two companies in North Kalimantan Province using water quality test analysis with grab sampling and estimating the potential loss of coal reserves using the rule of gradual changes and rule of nearest point methods as well as aerial photography. The research results show that in general the water use meets Class 3, namely: Water that can be used for cultivating freshwater fish, animal husbandry, water for irrigating crops, and/or other uses that require the same water quality as that use. Apart from that, PT XXX has built an overflow water channel into the PT YYY area without management approval, thus having a negative impact on PT YYY's mining plans which are dominated by peat land. Map of PT YYY's lost coal potential of 714,688 MT with an affected area of 15.16 hectares with details of 6.4 ha being the void area included in PT YYY's IUP area, 1.86 ha being the road and buffer zone area and 6.9 ha is a potential lost area of PT YYY.